Wacana Hukum Islam Tentang Perlindungan Anak - M, Muazzul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to examine further the Islamic legal discourse regarding child protection. Because in Islamic teachings, children have a special position. The child functions as a decoration that beautifies a family and soothes the eyes and heart. This research uses a qualitative approach. According to Creswell, theory in qualitative research uses lens theory or perspective theory to help researchers in various kinds of questions and how to collect data and analyze data. The results of the research show that Islamic teachings view children as having a special position covering a broad meaning, including as a gift from Allah to parents, society, nation and state, heirs of Islamic teachings (revelation of Allah SWT) who will one day prosper the world as rahmatan lil 'âlamîn and its environment.